Selective Radiosensitization of Human Cervical Cancer Cells and Normal Cells by Artemisinin Through the Abrogation of Radiation-Induced G2 Block. Issue 5 (1st June 2012) - Gong, Xiao-mei; Zhang, Qing; Torossian, Artour; Cao, Jian-ping; Fu, Shen
Abstract : Objective: Artemisinin has been shown to inhibit the growth of some human cancer cells. In this study, we investigated the radiosensitizing effects of artemisinin on cervical cancer cells and normal human fibroblast cells and also assessed some possible mechanisms for these effects. Materials and Methods: Two cervical cancer cell lines, HeLa and SiHa cells, and GM0639 normal human fibroblast cell line were treated with various concentrations of artemisinin plus radiation; the cell viability was tested using both 3-(4, 5-dimethylthiazolyl-2-y1)-2, 5-diphenyltetrazolium bromide and clonogenic assays. Radiation dose-modifying factors were measured by clonogenic survival assay. Annexin V/propidium iodide assay for the evaluation of apoptosis and cell cycle phase were determined by flow cytometry, and the expression of the cell cycle–associated proteins Wee 1 and cyclin B1 were analyzed by Western blot analysis. Results: Artemisinin showed higher cytotoxicity in cervical cancer cell lines, especially in SiHa cells, than in the normal cell line. In both clonogenic assay and apoptosis, artemisinin sensitized the HeLa cancer cells to the cytotoxicity of radiation, yielding a dose-modifying factor of 1.24, but not SiHa cancer cells and GM normal cells. At a dose of 110 nmol/L, artemisinin did not change the distribution of cell cycle in 3 tested cell lines, but artemisinin abrogated the radiation-induced G2 blockade. Analyses of G2-checkpoint-related proteins, the activation of Wee 1 and depression of cyclin B1 expression induced by radiation, could be restored to the control level by artemisinin. Conclusions: Given the unique cytotoxic profile of artemisinin on cancer cells and normal cells, artemisinin may be a potentially promising radiosensitizer through the regulation of the expression of G2 checkpoint-related proteins like Wee 1 and cyclin B1, and improve therapeutic ratios for the combination of artemisinin and ionizing irradiation in the treatment of patients with cervical cancer.